Comparative Evaluation of Clinical and Radiographic Success of MTA and Propolis in Pulpotomy of Primary Molars - Aghazadeh, Samaneh; Haghgoo, Roza; Mehran, Majid; Kadkhodaei, Fatemeh (Iranian Endodontic Journal, 2018)
Introduction: In this study, the results of using MTA and propolis in the pulpotomy of primary molar teeth are evaluated clinically and radiographically. Methods and Methods: A total of 25 healthy 4 to 8 year old children each having two carious primary molar teeth in one arch, based on inclusion criteria were selected. In each child, random assignment of the pulpotomy medicaments was done as follows: Group I, MTA in one side; Group II, Propolis in another side. All the pulpotomized teeth were evaluated at 3, 6, and 9 month clinically and radiographically, based on the scoring criteria system. Finally data was analyzed using GEE analysis. Results: Results showed that the effects of treatment and time on two scores were tested. Based on the results of this model, the chances of having clinical score 2, versus score 1 are about 2.7 times higher in MTA treatment than in propolis (P=0.001). Similarly, the chance of having a clinical score 2 relative to its one, at 9th month is approximately 6.8 times higher than the 3th month (P=0.000) and at 6th month is approximately 2.8 times higher than the 3th month (P=0.005). The chance of having higher scores of radiographies in treatment of propolis is approximately 6.5 times than that of MTA (P=0.000). Also, the chance of having higher scores of radiographic index at 6th month is approximately 5 times and at 9th month is approximately 27 times more than the 3th month (P=0.00). Conclusions: Based on the results of this experimental study, teeth treated with MTA showed more suitable clinical and radiographic results as compared to propolis at 9 months follow-up. Keywords: Mineral Trioxide Aggregate; Primary Teeth; Propolis; Pulpotomy